Water Into Wine: Using Social Policy Courses to Make MSW Students Interested in Politics. (3rd April 2021) - Meehan, Patrick
ABSTRACT: Social workers are making a name for themselves in national politics. Senators Kyrsten Sinema (D-AZ) and Debbie Stabenow (D-MI) have MSW degrees. The current chair of the Congressional Black Caucus, Karen Bass (D-CA), also has an MSW. Having social workers in elected office allows the profession to directly address the Grand Challenges of the 21st century. But given students' general disinterest in policy, let alone politics, getting students to take an interest in running for office can be a challenge. How can schools of social work make students interested in running for office? This study uses the results of a survey experiment from the Michigan Law & Social Work Study to show that referring to elected office as a way of making a difference in the community can make MSW students more interested in running for office. However, these results varied across the sample of 545 MSW students. Because of their practice interests and political socialization, many students are impervious to new messaging about the political system. This study finds that the difference-making message is most effective for micropractice students from less politically socialized households. The right messaging can make students more interested. Implications for social work education are discussed.